2020
DOI: 10.1038/s41372-020-00856-z
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in extremely low birth weight infants with bronchopulmonary dysplasia before hospital discharge

Abstract: Objective To compare pulmonary function in extremely low birth weight (ELBW) infants with bronchopulmonary dysplasia (BPD) studied at 34-36 weeks postmenstrual age (PMA) with a reference group of "healthy" infants born at 34-36 weeks. We hypothesized that ELBW infants have decreased functional residual capacity (FRC) and respiratory compliance (Crs). Study design Pulmonary function testing was performed at 34-36 weeks PMA in infants with BPD and within 96 h of age in infants delivered at 34-36 weeks. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Therefore, even the distal parenchyma might be functionally affected 42 . In infants with BPD, there are fewer and larger alveoli and less airway tethering of the airways through elastic components in the alveolar wall, which can affect elastic recoil 20,45 . Therefore, it is important to study lung function in BPD in a complex way with the full spectrum of iPFT methods so as not to neglect subtle changes in the maldeveloped lung.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, even the distal parenchyma might be functionally affected 42 . In infants with BPD, there are fewer and larger alveoli and less airway tethering of the airways through elastic components in the alveolar wall, which can affect elastic recoil 20,45 . Therefore, it is important to study lung function in BPD in a complex way with the full spectrum of iPFT methods so as not to neglect subtle changes in the maldeveloped lung.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, infants with BPD do not need to suffer from permanently abnormal lung function 18 . Using various infant pulmonary function testing (iPFT) methods, it has been shown that lung function in infants with BPD is reduced compared to healthy term controls 19–21 . On the other hand, functional deficits similar to infants with BPD may also be found in preterm infants without the diagnosis of BPD 22–25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some reports of follow-up lung function tests of BPD infants showing these children continue to have abnormal baseline spirometry with significant airway obstruction 38 , 39 . Furthermore, a previous study also reported that premature infants with BPD before hospital discharge have decreased lung function compared to healthy infants 40 .…”
Section: Discussionmentioning
confidence: 88%
“…But, due to the immature lung development, many premature babies are prone to respiratory distress syndrome (RDS), apnea, pulmonary hemorrhage and other respiratory diseases, and often need mechanical ventilation [1][2][3]. Among them, because of smaller gestational age and lower birth weight, very low birth weight infants (VLBWIs) are vulnerable to pulmonary hemorrhage, which can result in respiratory failure, death and other chronic consequences [4][5].…”
Section: Introductionmentioning
confidence: 99%